Superficial Muscular Aponeurotic System–Pedicled Flaps for the Reconstruction of Facial Defects: Clinical application and Anatomical Basis. Issue 7 (July 2020) - Zhou, Muran; Zhong, Aimei; Chen, Jialong; Sun, Yang; Wang, Zhenxing; Xiong, Lingyun; Guo, Ke; Wang, Rongrong; Guo, Nengqiang; Sun, Jiaming
Summary: Background: Application of distant skin flaps in facial defect reconstruction has limitations such as leaving a patch like appearance and being restricted by the length of the vascular pedicles. Leveraging the abundance of blood supply from superficial muscular aponeurotic system (SMAS), a local skin flap pedicled by SMAS can be used to avoid the aforementioned problems. Herein, we report the clinical application as well as the anatomical study of SMAS-pedicled skin flaps. Methods: This study enrolled patients who underwent facial defect reconstruction surgery between 2013 and 2018 using SMAS-pedicled skin flaps. The flaps were designed according to the size and location of the defect. A follow-up was performed to evaluate the treatment outcomes and incidence of adverse events. In addition, six cadaveric heads were used to perform an anatomical study on the distribution and blood supply of SMAS. Results: Twenty-three cases underwent the defect reconstruction surgery in the frontal regions (three cases), temporal region (four cases), periocular region (four cases), nasal region (seven cases), and other regions (five cases). All the flaps survived well. During the follow-up period up to 12 months, the flaps showed a satisfactory appearance, blood supply, and elasticity. The distribution and blood supply of SMAS at different anatomical regions have been successfully observed. Abundant vascular networks could be found in the SMAS layer. Conclusion: Based on the broad distribution of SMAS and the abundant blood supply, an SMAS-pedicled skin flap could be flexibly designed and versatilely used to reconstruct post-traumatic or post-excisional facial defects.